Psychological Determinants Of Voluntary Quitting Among Four Star Hotel Personnel: Determinan Psikologis Berhenti Sukarela Pada Personel Hotel Bintang Empat - Ayesha Dira Parahita; Netania Emilisa; Radita Finanda Ramadhanti; Beta Oki Baliartati; Faiza Nur Hakim (Indonesian Journal of Law and Economics Review, 2026)
General Background Human resources represent strategic assets crucial for organizational operational success and global competitive advantage. Specific Background The hospitality industry faces significant challenges maintaining workforce stability due to intense customer service demands, uncertain working hours, and shift-based operational systems. Knowledge Gap Although the hotel sector experiences exceptionally high voluntary departure rates, the concurrent evaluation of negative individual psychological states and organizational attachment metrics remains limited. Aims This study investigates how workplace happiness, work hopelessness, perceived organizational support, and job embeddedness predict the intention to leave among four-star hotel employees in North Jakarta. Results Quantitative multiple regression analysis of 110 respondents reveals that happiness at work, perceived organizational support, and job embeddedness significantly decrease the intention to leave. Conversely, work hopelessness significantly drives the desire to seek alternative employment. Novelty This research identifies job embeddedness as the most substantial psychological deterrent against turnover intention within high-stress hospitality environments. Implications Hospitality management must prioritize employee attachment strategies, transparent career development, and routine workload evaluations to foster retention and ensure long-term operational stability. Highlights Job embeddedness serves as the strongest deterrent against turnover intention. Work hopelessness significantly increases the desire to leave the organization. Management must prioritize career development and workload evaluations to improve retention. Keywords Turnover Intention; Job Embeddedness; Organizational Support; Work Hopelessness; Happiness At Work